2017
DOI: 10.1007/s10646-017-1796-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water chemistry and surface contact on the toxicity of silver nanoparticles to Bacillus subtilis

Abstract: The growing use of silver nanoparticles (AgNPs) has created concerns about its potential impacts on natural microbial communities. In this study, the physicochemical properties of AgNPs and its toxicity on natural bacteria Bacillus subtilis (B. subtilis) were investigated in aqueous conditions. The characterization data showed that AgNPs highly aggregated in aqueous conditions, and the hydrodynamic diameter of AgNPs in aqueous conditions was larger than its primary size. The studied AgNPs was less toxic to B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The nanomaterial coating may also be a confounding factor in toxicity assessments [20,24,30,46], though oleic acid was used in the present study and is regarded as non-toxic [47]. AgNPs coated with fatty acid (oleic acid), used in the present study, are quite stable and do not dissolute as much silver ion as previously reported [22,48]. The limited release of silver ion from the AgNPs used might explain the observed limited toxicity in fish embryos.…”
Section: Discussionmentioning
confidence: 59%
“…The nanomaterial coating may also be a confounding factor in toxicity assessments [20,24,30,46], though oleic acid was used in the present study and is regarded as non-toxic [47]. AgNPs coated with fatty acid (oleic acid), used in the present study, are quite stable and do not dissolute as much silver ion as previously reported [22,48]. The limited release of silver ion from the AgNPs used might explain the observed limited toxicity in fish embryos.…”
Section: Discussionmentioning
confidence: 59%
“…The morphologic and structural properties of bacteria between B. subtilis and SEBS was monitored using a scanning electron microscope (SEM) and transmission electron microscopy (TEM). The bacteria of B. subtilis and SEBS was concentrated via centrifugation at 3, 000 rpm, and immersed in a 5% glutaraldehyde solution for 24 h [24]. Se concentration in the supernatant and precipitate of B. subtilis and SEBS fermented medium was calculated using atomic absorption spectrometry and the live bacteria was enumerated with yeast extract peptone dextrose medium after term serial dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The morphological and structural properties of B. subtilis yb-114,246 and SEBS were monitored using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). B. subtilis yb-114,246 and SEBS were concentrated via centrifugation at 3, 000 rpm, and immersed in a 5% glutaraldehyde solution for 24 h [19]. Se concentration in the supernatant and precipitate of B. subtilis yb-114,246 and SEBS fermented medium was calculated using atomic absorption spectrometry and the live bacteria were enumerated with yeast extract peptone dextrose medium after term serial dilution.…”
Section: Preparation and Analyses Of Bs And Sebsmentioning
confidence: 99%